A4NH flagship 5: Improving human health - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
Agriculture enhances access to food and improves livelihoods, but in some cases, may also be linked with increased risks of disease transmission. Historically, CGIAR research has explored agriculture and health interactions related to irrigation and vector-borne diseases, use of wastewater in agriculture, integrated pest management (IPM), and emerging and neglected zoonotic diseases. Research that bridges disciplinary divisions and enhances links between agriculture and health provides a largely untapped opportunity to improve the health and livelihoods of poor people, especially in rural areas where ill health may be the most critical pathway for staying or becoming poor, and undermines the benefits of agricultural development.